Identification of Concomitant Infection with Chlamydia trachomatis IncA-Negative Mutant and Wild-Type Strains by Genomic, Transcriptional, and Biological Characterizations - Suchland, Robert J. (American Society for Microbiology (ASM), 2008)
Clinical isolates of Chlamydia trachomatis that lack IncA on their inclusion membrane form nonfusogenic inclusions and have been associated with milder, subclinical infections in patients. The molecular events associated with the generation of IncA-negative strains and their roles in chlamydial sexually transmitted infections are not clear. We explored the biology of the IncA-negative strains by analyzing their genomic structure, transcription, and growth characteristics in vitro and in vivo in comparison with IncA-positive C. trachomatis strains. Three clinical samples were identified that contained a mixture of IncA-positive and -negative same-serovar C. trachomatis populations, and two more such pairs were found in serial isolates from persistently infected individuals. Genomic sequence analysis of individual strains from each of two serovar-matched pairs showed that these pairs were very similar genetically. In contrast, the genome sequence of an unmatched IncA-negative strain contained over 5,000 nucleotide polymorphisms relative to the genome sequence of a serovar-matched but otherwise unlinked strain. Transcriptional analysis, in vitro culture kinetics, and animal modeling demonstrated that IncA-negative strains isolated in the presence of a serovar-matched wild-type strain are phenotypically more similar to the wild-type strain than are IncA-negative strains isolated in the absence of a serovar-matched wild-type strain. These studies support a model suggesting that a change from an IncA-positive strain to the previously described IncA-negative phenotype may involve multiple steps, the first of which involves a translational inactivation of incA, associated with subsequent unidentified steps that lead to the observed decrease in transcript level, differences in growth rate, and differences in mouse infectivity.